Investigating the relationship between job insecurity and health in Europe: a focus on cardiovascular disease - Sivri, Kalliopi (2019)
Background: The economic crisis, which commenced in 2008, had several negative consequences for both nations and individuals. The overall economic situation of nations affected growth, development and employment opportunities. Consequently, unemployment levels and job insecurity for those employed both increased. This thesis aims to explore the impact of job insecurity on a specific group of employees: those affected by cardiovascular disease. Specifically, the thesis aims to explore the interactions between job insecurity and other work-related factors and add knowledge on how employees who had a heart attack and returned to work experience employment protection and social support at work. The thesis also aims to explore the role of work-related factors and employment protection in these employees’ recovery and transition back to work while managing their cardiovascular disease.